2023
DOI: 10.1002/iid3.762
|View full text |Cite
|
Sign up to set email alerts
|

Role of signal transduction pathways in IL‐1β‐induced apoptosis: Pathological and therapeutic aspects

Abstract: Background: Interleukin-1β (IL-1β) is a pro-inflammatory cytokine mainly produced by monocytes and macrophages with a wide range of biological effects. Evidence has shown that IL-1β plays a vital role in the process of apoptosis; however, the specific mechanisms, by which IL-1β induces apoptosis, vary due to different cellular and experimental conditions. Therefore, this present reviewstudy aimed to systematically review the association between the molecular mechanisms of IL-1β-induced apoptosis in pathologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 104 publications
(166 reference statements)
1
3
0
Order By: Relevance
“…A positive feedback loop develops between TNFα, NF-κB, and IL1β, accentuating leukocyte formation with further activation of inflammation and apoptosis (Kaur et al 2021). Supporting this, the predominance of M1 macrophages in DM and its role in promoting DCM has been previously reported (Lehrke et al 2004;Wang et al 2023;Coggins and Rosenzweig 2012).…”
Section: Discussionsupporting
confidence: 56%
“…A positive feedback loop develops between TNFα, NF-κB, and IL1β, accentuating leukocyte formation with further activation of inflammation and apoptosis (Kaur et al 2021). Supporting this, the predominance of M1 macrophages in DM and its role in promoting DCM has been previously reported (Lehrke et al 2004;Wang et al 2023;Coggins and Rosenzweig 2012).…”
Section: Discussionsupporting
confidence: 56%
“…The inhibition of NLRP3 inflammasome can lead to the decreased expression of IL-1β (30). Consequently, the IL-1βinduced apoptosis can be alleviated through NF-κB, MAPKs and PI3K/Akt signaling pathway (31). In our previous study (16), we also found melatonin inhibited NLRP3 inflammasome to relieve apoptosis in DCD hearts.…”
Section: Discussionmentioning
confidence: 77%
“…Overactivity of these pathways results in NFκB activation and subsequently increased levels of pro-inflammatory cytokines, especially IL1β and IFNγ. In our study, the elevated IL1β levels may have been regulated by these two pathways and NFκB[ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%